Coupled Short- and Medium-Term Geophysical Signals at Etna Volcano: Using Deformation and Strain to Infer Magmatic Processes From 2009 to 2017 - Aloisi, Marco; Bonaccorso, Alessandro; Cannavò, Flavio; Currenti, Gilda M. (Frontiers in Earth Science, 2018)
Due to the frequent eruptive activity of Etna volcano, it is of primary importance to interpret the near-real time geophysical data as best as possible in order to understand the unrest vs. eruptive timescales. After the main flank eruption of 2008-2009 and until 2017, Etna volcano was characterized by a lively eruptive activity of different phases. These comprised 44 lava fountain episodes that formed a new crater named New South East Crater (NSEC) during 2011-2013, two sequences of close episodes of lava fountains from the Voragine crater (VOR) on 3-5 December 2015 (4 events) and May 18-21, 2016 (3 events), as well as some periods of summit effusive activity with a more prolonged supply of lava flows during 2014. Several studies have described and modelled single episodes of lava fountains of both the NSEC and VOR. In particular, during lava fountainings the high precision data from borehole strain-meters revealed short-term changes, which allowedinference into the source of decompression at a shallow level (shallow plumbing system) of at ~ sea level for the events of the NSEC and at deeper level (~2-5 km b.s.l.) for those of VOR, respectively. In this study, we also considered the middle-term volcano recharging/discharging periods preceding/accompanying the different eruptive phases during 2009-2017, and through the deformation recorded by the permanent GPS network, we constrained the position of the sources. Together with the modelling deduced from the strain-meter data we produce a more complete representation of the different sources that characterized the different periods both in the middle-term (i.e. the preparatory phases showing inflation and the eruptive phases showing deflation) and in the short-term (i.e. the fast discharge associated with each eruptive event). Our highly resolved modelling explains the pathway of magma from the intermediate-shallow plumbing system to the surface. Our results are consistent with petrological constraints on the spatio-temporal evolution of magma transfer and storage.